Casas de piedra : sierra, mar y llanura (Summa+, 1997)
Del arquitecto José Ignacio Díaz: Casa Minetti, Córdoba. San Martín-Lonné; Casa constantino, Uruguay. Joselevich, I.; Casa en la llanura, Uruguay